Art and Reality (Aspects of the Analysis of Artistic Creation in Pre-Marxist Aesthetics and Their Methodological Significance) - Gudaitytė, Rūta (Problemos, 1968)
The paper attempts to clear up the aspects of the analysis of artistic creation in pre-Marxist aesthetics and its methodology, for the achievements of pre-Marxist aesthetics have exercised great influence on Marxist, including Soviet aesthetics, thought. Marxist methodology considers art as spiritual and practical activity which is distinct from other forms of activity by its purpose and functions it performs. The functions it performs determine a corresponding structure. Therefore the result of artistic creation - works of art which are created on the basis of cognition of the world - is an intermediary between the artist and the perceiver.